SPOROTRICHOSIS: AN EMERGING DISEASE FROM A UNIQUE HEALTH PERSPECTIVE - Kattah, Hoxana Xavier Lopes; Pereira, Jaqueline Aparecida Sousa; Couto, Diogo Sena; Alexandrowitsch , Fátima Christina França; Reis, Fábio Nogueira; Nogueira, Vinicius José Moreira; Alves, Breno Henrique; Peconick, Ana Paula (Seven Editora, 2025)
Sporotrichosis is a mycotic infection caused by a complex of fungal species of the genus Sporothrix. The domestic cat plays a crucial role in the transmission of the disease, being considered the main host and source of infection for humans, which accentuates its impact on public health. This study aimed to morphologically characterize Sporothrix spp. isolated from a feline diagnosed with sporotrichosis, using scanning electron microscopy (SEM). The methodology consisted of collecting exudate from the lesion followed by isolation and cultivation of the fungus on Sabouraud Dextrose Agar medium, incubated at 25°C for 12 days. Processing followed a standard protocol for preparing biological samples for analysis in the SEM, involving cutting, dehydration in increasing series of acetone, critical point, gold plating and mounting on stubs. The electromicrographs obtained on the TESCAN-CLARA SEM showed high resolution, allowing the morphological characteristics of the fungus to be identified. The phenotypic parameters described by Marimon et al. (2008) were used to characterize the findings of this study. The hyphae observed were classified as septate, narrow and branched, with dematiaceous and spherical conidia at the ends. The conidia were thick-walled, wrinkled in texture and small in diameter, ranging from oval to globose.DOI: https://doi.org/10.56238/sevened2025.021-022